Environmental stress-induced testis differentiation: Androgen as a by-product of cortisol inactivation - Fernandino, Juan Ignacio (2013)
This review deals with the gonadal masculinization induced by thermal stress in fish with focus on the action of 11b-hydroxysteroid dehydrogenase (11b-HSD) as this mechanism key transducer. High temper- atures have been reported to produce male-skewed sex ratios in several species with TSD (temperature- dependent sex determination), and in some of them, this process was reported to be associated with high levels of cortisol, the hormone-related stress in vertebrates, during early gonad development. In addition, in pejerrey larvae reared at high-masculinizing temperatures, 11-ketotestosterone (11-KT), the main and most potent androgen in fish, was also detected at high levels. In testicular explants, cortisol induced the synthesis of 11-KT, suggesting that its synthesis could be under the control of the stress axis at the time of gonadal fate determination. 11b-HSD is one of the enzymes shared by the glucocorticoid and androgen pathways; this enzyme converts cortisol to cortisone and also participates in the finals steps of the syn- thesis of the 11-oxigenated androgens. Based on these data and literature information, here we propose that the masculinization induced by thermal stress can be considered as a consequence of cortisol inac- tivation and the concomitant synthesis of 11-KT and discussing this as a possible mechanism of mascu- linization induced by different types of environmental stressors.